Lightweight Mobile and Wireless Systems: Technologies, Architectures, and Services. (19th January 2011) - Skianis, Charalabos; Granelli, Fabrizio; Chatzimisios, Periklis; Verikoukis, Christos; Devetsikiotis, Michael
Abstract :